2001
DOI: 10.1126/science.291.5505.878
|View full text |Cite
|
Sign up to set email alerts
|

Bakers' Yeast, a Model for Fungal Biofilm Formation

Abstract: Biofilms are formed by the aggregation of microorganisms into multicellular structures that adhere to surfaces. Here we show that bakers' yeast Saccharomyces cerevisiae can initiate biofilm formation. When grown in low-glucose medium, the yeast cells adhered avidly to a number of plastic surfaces. On semi-solid (0.3% agar) medium they formed "mats": complex multicellular structures composed of yeast-form cells. Both attachment to plastic and mat formation require Flo11p, a member of a large family of fungal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
686
2
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 537 publications
(721 citation statements)
references
References 16 publications
28
686
2
5
Order By: Relevance
“…The pCF56 also suppressed the filamentous growth defect of a diploid flo8 mutant ( Figure 1B). ScFlo8 has been shown to be essential for the formation of biofilm-like colonies on media with low percentage agar (Reynolds and Fink, 2001), and we found that the defect could be partially suppressed by pCF56 ( Figure 1C). pCF56 contains a gene that encodes a putative protein of 817 aa, with a small region (amino acids 30 -92) highly similar to amino acids 72-154 of ScFlo8 (Figure 2A).…”
Section: Cloning Of a C Albicans Homologue Of Scflo8 By Complementationmentioning
confidence: 60%
“…The pCF56 also suppressed the filamentous growth defect of a diploid flo8 mutant ( Figure 1B). ScFlo8 has been shown to be essential for the formation of biofilm-like colonies on media with low percentage agar (Reynolds and Fink, 2001), and we found that the defect could be partially suppressed by pCF56 ( Figure 1C). pCF56 contains a gene that encodes a putative protein of 817 aa, with a small region (amino acids 30 -92) highly similar to amino acids 72-154 of ScFlo8 (Figure 2A).…”
Section: Cloning Of a C Albicans Homologue Of Scflo8 By Complementationmentioning
confidence: 60%
“…4) . Although filamentous growth is not essential for the formation of biofilms (Hawser and Douglas 1994;Reynolds and Fink 2001;Martinez and Casadevall 2007;Cushion et al 2009), hyphae strengthen the biofilm structure and provide strong and expanded scaffolds for the deposition of extracellular matrix materials and other cells (Ramage et al 2002;Richard et al 2005). Hyphae of C. albicans are known to penetrate host tissues and even denture materials, and thus it is not surprising that there are many hyphal-specific adhesins that help anchor hyphae firmly to the substrate.…”
Section: Morphogenesis In Community Developmentmentioning
confidence: 99%
“…In particular, naturally occurring S. cerevisae colonies exhibit a structured pattern that seems related to an extracellular matrix material and is rapidly lost under laboratory conditions [17]. Despite their smooth colony morphology in the lab, budding yeast cells are also capable of forming biofilms [18] and multicellular stalk-like structures that might be linked to spore dissemination [19,20]. Budding yeast can stably exist as either haploid or diploid cells, which, under favourable growth conditions, divide by budding.…”
Section: Fungal Morphogenesis -An Overviewmentioning
confidence: 99%